2022
DOI: 10.11604/pamj.2022.42.163.35161
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of patients leaving against medical advice in government-subsidized hospitals: a descriptive retrospective study

Abstract: Introduction this study aimed to determine the prevalence of leaving against medical advice (LAMA) in the local context and the associated predictors to help develop effective strategies to reduce its likelihood. Methods this study employed a retrospective approach using medical records of the 16233 patients between 2016 and 2020 at various government-subsidized hospitals in the Hail region of Saudi Arabia. Results the prevalence of LAMA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…23 In most cases, Paul et al found out that the frequency and causes for LAMA vary according to the ailment, geographical region, and type of healthcare system. 24 All of these problems were worsened by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…23 In most cases, Paul et al found out that the frequency and causes for LAMA vary according to the ailment, geographical region, and type of healthcare system. 24 All of these problems were worsened by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%